2020
DOI: 10.1159/000506277
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Therapies in the Treatment of Focal Segmental Glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is one of the most frequent and severe glomerular kidney disease with frequent progression to end-stage renal disease and a high rate of recurrence in renal transplantations. Due to intolerance or resistance to the current immunomodulatory treatments, the management of FSGS is a therapeutic challenge. Over the last few years, development in extracorporeal therapies has shown potential beneficial outcomes in drug-resistant and recurrent FSGS patients. Thus, this study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Notably, the possibility to clearly discriminate PD patients with FSGS and those affected by other PRDs could be useful for the stratification of the 30% of children with ESKD who are referred for transplantation but had not undergone a renal biopsy, and around to 20% of which are diagnosed with possible glomerulonephritis 26 , 54 . In fact, notwithstanding the advances in immune-modulating and extracorporeal therapies, FSGS remains a challenge for pediatric nephrologists, as response to treatment is low and recurrence can occur after renal transplantation in a significant percentage of cases 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the possibility to clearly discriminate PD patients with FSGS and those affected by other PRDs could be useful for the stratification of the 30% of children with ESKD who are referred for transplantation but had not undergone a renal biopsy, and around to 20% of which are diagnosed with possible glomerulonephritis 26 , 54 . In fact, notwithstanding the advances in immune-modulating and extracorporeal therapies, FSGS remains a challenge for pediatric nephrologists, as response to treatment is low and recurrence can occur after renal transplantation in a significant percentage of cases 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Many reasons may explain this condition, but recent data suggest that the use of calcineurin inhibitors (CNI), such as tacrolimus and cyclosporine A, primary immunosuppressive agents employed in FSGS, and in general for corticosteroid-dependent and resistant nephrotic syndrome, seems to play a pivotal role 12 , 13 . CNI, in fact, may cause fibrosis in kidney and other organs through the increment of TGFβ1 expression and EMT activation 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts at non-selective removal or specific blockade of putative circulating factors have been performed, especially in case of post-transplant FSGS recurrence, which represents a particularly challenging and largely unmet medical need. The use of plasma exchange, immunoadsorption and LDL-apheresis methods in patients who did not respond to available therapies have been reported with variable outcomes (178), but methods to selectively remove circulating permeability factor candidates have not been reported yet. A phase 2 randomized clinical trial is under way to assess the effect of the anti-CD40 monoclonal antibody Bleselumab, which blocks the interaction between CD40 and its ligand, in preventing FSGS recurrence (NCT02921789).…”
Section: Treatment Of Primary Fsgsmentioning
confidence: 99%
“…The contribution of circulating factors to nephrotic syndrome pathogenesis has raised interest in extracorporeal therapies such as plasma exchange (PE), immunoadsorption (IAS) and lowdensity lipoprotein apheresis (LDL-A) 7 . Plasma exchange has been the most widely studied, though randomized controlled study data are largely unavailable and reported cases have invariably shown PE use in conjunction with other immunosuppressive therapy.…”
mentioning
confidence: 99%
“…The contribution of circulating factors to nephrotic syndrome pathogenesis has raised interest in extracorporeal therapies such as plasma exchange, immunoadsorption, and low-density lipoprotein apheresis. 8 Plasma exchange has been the most widely studied, although randomized controlled study data are largely unavailable, and reported cases have invariably shown plasma exchange use in conjunction with other immunosuppressive therapy. Semi-selective immunoadsorption is a modified plasma exchange whereby high-affinity absorption columns containing specific ligands could facilitate selective circulating factor removal.…”
mentioning
confidence: 99%